Finite element analysis of active metal braised semiconductor package for warpage reduction - Moran, Roberto Louis P. (Animo Repository, 2022)
Warpage is considered as a major concern in semiconductor packaging devices due to possible reliability and functionality failures. With the miniaturization of the electronic devices with the simultaneous increased functionality makes the new electronic devices susceptible to quality and reliability issues. Warpage induced by thermal processes in production causes the packages to fail. The active metal brazed (AMB) ceramic substrate is a key semiconductor packaging technology for automotive and power module electronics. The AMB is a composite of copper, ceramic, plastic, gel, and adhesives, with additional components depending on the application. Cutting back-side channel patterns can counter the warpage due to the deformation induced from the inharmonius mechanical properties and varying geometries of each composite material. This research uses finite element analysis (FEA) coupled with optimization techniques to generate a method of designing back-side channel patterns to minimize the warpage. The FEA is verified using real-world data from related studies.